2022
DOI: 10.3390/v14122659
|View full text |Cite
|
Sign up to set email alerts
|

Would Zika virus Infection in Pregnancy Be a Sentence of Poor Neurological Prognosis for Exposed Children? Neurodevelopmental Outcomes in a Cohort from Brazilian Amazon

Abstract: Infections with Flavivirus in pregnant women are not associated with vertical transmission. However, in 2015, severe cases of congenital infection were reported during the Zika virus outbreak in Brazil. More subtle infections in children born to mothers with ZIKV still remain uncertain and the spectrum of this new congenital syndrome is still under construction. This study describes outcomes regarding neurodevelopment and neurological examination in the first years of life, of a cohort of 77 children born to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Of the 77 children in the Abtibol-Bernardino [ 30 ] cohort, 71 were followed up regarding their anthropometric measurements and growth velocity. Of that group, 6 children were excluded because they attended a single assessment or went more than 12 months between assessments.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 77 children in the Abtibol-Bernardino [ 30 ] cohort, 71 were followed up regarding their anthropometric measurements and growth velocity. Of that group, 6 children were excluded because they attended a single assessment or went more than 12 months between assessments.…”
Section: Resultsmentioning
confidence: 99%
“…The high incidence of ZIKV in the period of 2015–2016 in Brazil may have significantly affected GV in children exposed to ZIKV. In this study, we describe the GV alterations of children exposed in utero to ZIKV when both mothers and children were followed up in a cohort in the Brazilian Amazon [ 21 , 30 ]. We showed that 24.2% of children had inadequate GV, and the frequency of inadequate GV was similar between microcephalic and non-microcephalic patients (approximately 24%), indicating the need for microcephalic and non-microcephalic patients to be evaluated constantly and without predilections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations